Implications of the Theory of Meaning in Language Learning: Perspectives on Language Acquisition on the ESP Classroom - Maulida, Ida; Zuriyati, Zuriyati; Setiadi, Samsi (Newinera Publisher, 2024)
This study investigates the role of language in the theory of meaning on communication in the education. The aims of the study to examine how theory of meaning emphasize the contextual word and phrases. The study uses qualitative descriptive by using case studies. The sample of the study consisted of 35 students’ on ESP Classroom at Universitas Subang. Data collection techniques by using questionnaires, interview, and observation. The questionnaire used a Likert Skale focus on students’ response regarding the influence of context on word meaning, the effectiveness of visual references. Interviews focus on exploring students’ understanding of context on word meanings and perceptions of referential on their fields of study. Based on the result of study show that the majority of students’ (43%-57%) agree that contextual comprehend significantly influences their focus of the meaning of words. Additionally, the data show that theories of meaning as important in accurately interpreting field-specific vocabulary, enabling them to understand differences in meaning that emerge between contexts.